(untitled) (Hekima Review, 2016)
The book “AIDS: 30 Years Down the Line...” offers a comprehensive account of the efforts made by the Catholic Church in the fight against the pandemic of HIV/AIDS in sub-Saharan Africa. Published in 2012 by the African Jesuit AIDS Network (AJAN), this masterpiece is a reflection of what Christian experts in academia, practitioners and activists think about the effectiveness of the Church’s response in the past thirty years since the emergency of the AIDS scourge. In short, the book offers “a rich menu for all who wish to acquaint themselves with current conversations about HIV/AIDS from the perspectives of faith-based organizations and initiatives in the Catholic Church (18).”